Protein Scaffold‐Based Multimerization of Soluble ACE2 Efficiently Blocks SARS‐CoV‐2 Infection In Vitro and In Vivo. Issue 27 (27th July 2022) - Kayabolen, Alisan; Akcan, Ugur; Özturan, Doğancan; Ulbegi‐Polat, Hivda; Sahin, Gizem Nur; Pinarbasi‐Degirmenci, Nareg; Bayraktar, Canan; Soyler, Gizem; Sarayloo, Ehsan; Nurtop, Elif; Ozer, Berna; Guney‐Esken, Gulen; et al.
Abstract: Soluble ACE2 (sACE2) decoys are promising agents to inhibit SARS‐CoV‐2, as their efficiency is unlikely to be affected by escape mutations. However, their success is limited by their relatively poor potency. To address this challenge, multimeric sACE2 consisting of SunTag or MoonTag systems is developed. These systems are extremely effective in neutralizing SARS‐CoV‐2 in pseudoviral systems and in clinical isolates, perform better than the dimeric or trimeric sACE2, and exhibit greater than 100‐fold neutralization efficiency, compared to monomeric sACE2. SunTag or MoonTag fused to a more potent sACE2 (v1) achieves a sub‐nanomolar IC50, comparable with clinical monoclonal antibodies. Pseudoviruses bearing mutations for variants of concern, including delta and omicron, are also neutralized efficiently with multimeric sACE2. Finally, therapeutic treatment of sACE2(v1)‐MoonTag provides protection against SARS‐CoV‐2 infection in an in vivo mouse model. Therefore, highly potent multimeric sACE2 may offer a promising treatment approach against SARS‐CoV‐2 infections. Abstract : Multimeric soluble angiotensin‐converting enzyme 2 (sACE2) generated via SunTag/MoonTag scaffolds enhanced neutralization capacity of monomeric sACE2 more than 100‐fold against pseudoviruses of variants of concern (VOC) and live severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). Therapeutic treatment of sACE2(v1)‐MoonTag provides protection against SARS‐CoV‐2 infection in mice. These results suggest the potential use of multimeric sACE2 for SARS‐CoV‐2 neutralization in clinical setting.